A review of pain behaviour assessment scales in horses - Luna, Stelio P L [UNESP] (Mark Allen Group, 2025)
Most clinical problems involve pain, and there are a greater number of pain assessment scales available for horses than any other species. Identifying pain is vital to assist with the analgesic strategy. This review guides the clinician in selecting the most appropriate equine full-body or facial pain assessment scales, based on the type (somatic or visceral), progression (acute and chronic) and location of pain (limbs, thoracolumbar, head, soft tissue, abdomen), applied to horses and foals through information on the usability, limitations, reliability and validity attributes of each scale. The confounding factors influencing pain assessment, suggestions for the future and free resources available for assessing pain in horses are presented in a practical and ready-to-use way.